Utilization of Sugars by Two Isolates of Cenococcum graniforme - Kumar, Dinesh; Thapar, H. S. (Indian Forester, 1968)
The utilization of sugars by two isolates of Cenococcum graniforme, a mycorrhizal fungus, was studied chromatographically. Whereas kail isolate (K 1) had preference for glucose and related compounds, deodar isolate (D 1) preferred fructose and fructose oriented compounds. Maltose and sucrose were utilized by indirect pathway by these fungi. Raffinose and starch were not hydrolysed. Utilization of maltose by K1 was slowed down in the presence of sucrose but enhanced in preseace of xylose.